Hubungan Perilaku Konsumsi Kafein, Tingkat Kecemasan Dan Perilaku Merokok Dengan Kejadian Gastritis Di SMK Kesehatan Mulia Karya Husada Tahun 2023 - Aisyah Aisyah; Nina Nina; Solehudin Solehudin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Gastritis is inflammation in the stomach due to an unhealthy lifestyle. If not treated immediately, it can cause damage to cells in the digestive system and if it lasts for a long time, it can cause stomach cancer. The aim of this research is to determine the relationship between caffeine consumption behavior, anxiety levels and smoking behavior with the incidence of gastritis at Mulia Karya Husada Health Vocational School in 2023. Quantitative research method with a cross sectional approach. The sampling technique used was Total Sampling with a sample size of 123 respondents, data collection using a questionnaire distributed using Google Form. The statistical test used in this research is the Chi Square test. Based on the results of the Chi Square test, it shows that the significance value between caffeine consumption behavior and gastritis (p-value = 0.003), the significance value between the level of anxiety and gastritis (p-value = 0.001) and the significance value between smoking behavior and gastritis (p-value = 0.025). In conclusion, there is a relationship between caffeine consumption behavior, anxiety levels and smoking behavior and the incidence of gastritis at Mulia Karya Husada Health Vocational School in 2023. The incidence of gastritis at Mulia Karya Husada Health Vocational School is relatively high, which is caused by caffeine consumption behavior, anxiety levels, and smoking behavior. So it is important to create programs such as a healthy canteen, game based learning and education about the dangers of smoking and supervision carried out by Mulia Karya Husada Health Vocational School to reduce the incidence of gastritis in students